2012
DOI: 10.1186/1477-7819-10-279
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the kidney: case report and review of literature

Abstract: BackgroundRenal primitive neuroectodermal tumor (rPNET) as a member of Ewing’s sarcoma family is extremely rare and usually occurs in children and young adults. Most literature about rPNET was isolated case reports.Case presentationWe reported a case of 45-year-old man with the complaint of right flank pain. Computerized tomography (CT) scan demonstrated a large substantive tumor involving the lower pole of the right kidney. Then the patient underwent radical nephrectomy. Pathologic characteristics and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Imaging findings, such as huge renal mass (more than 10 cm in diameter) is prevalent (6,7,11). As the tumor is highly aggressive, it is often diagnosed at an advanced stage with distant metastasis, with lung being one of the most common sites (4,12,13). However, some studies, such as Thyavihally et al (2008) showed that patients mostly had localized disease at presentation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging findings, such as huge renal mass (more than 10 cm in diameter) is prevalent (6,7,11). As the tumor is highly aggressive, it is often diagnosed at an advanced stage with distant metastasis, with lung being one of the most common sites (4,12,13). However, some studies, such as Thyavihally et al (2008) showed that patients mostly had localized disease at presentation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular testing is useful in situations with a confusing immunohistochemical profile. The diagnosis of renal PNET always needs to include tumor morphology, immunostaining profile and sometimes genetic mutations (10).…”
Section: Discussionmentioning
confidence: 99%
“…There is a slight male predominance seen in the literature for PNET in general as well as renal PNET. The tumours tend to be very large and maximum diameter of renal PNET is more than 10 cm (average 12.4 cm) with size ranging from 4 to 24 cm [4,5] . This difference in size may be a differentiating feature from renal carcinoma as the tumours of renal cell carcinoma can be smaller than 3cm and can be multi-focal in the setting of Von hippel Lindau syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT demonstrated intense2-[18F]flouro-2-deoxy-glucose (FDG) uptake (standardised uptake value[SUV] maximum 11.8) similar to other renal tumours [4] . Pain, palpable mass and hematuria are the most common symptoms [5] .…”
Section: Case Reportmentioning
confidence: 94%
See 1 more Smart Citation